Polyfunctional Si-N Containing Modifiers ofIndustrial Polymers: Synthesis, Properties and Use - LEKISHVILI, N.; KEZHERASHVILI, M.; LEKISHVILI, G. (Asian Journal of Chemistry, 2010)
Polyfunctional silicon-organic oligomers containing Si-N, Si-Ogroups, as well as arylene and heteroarylene fragments in the main chainsof macromolecules are reviewed. The methods of their synthesis andmechanisms of the formation are discussed. The properties and spheresof their application are considered.